EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM POSING DAN PROBLEM SOLVING PADA MATERI TRIGONOMETRI DITINJAU DARI KREATIVITAS PESERTA DIDIK KELAS XI IPA SMA SE-KABUPATEN KUDUS TAHUN PELAJARAN 2013/2014 - Sugihardjo Sugihardjo; Mardiyana Mardiyana; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of this research was to determine the effect of learning models on mathematics achievement and learning interest viewed from the students creativity. The learning model compared were problem posing, problem solving and direct instruction. The type of the research was a quasi experimental research with factorial design 3 x 3. The population was the students of senior high school in Kudus regency on academic year 2013/2014. The size of the sample was 278 learnes consisted of 98 students in the first experimental class, 81 students in the second experimental class and 99 students in the control class. The instrument used were mathemathics achievement test and questioner. The data was analyzed using analysis variance of two ways with unbalanced of cell. The conclusions of the research were as follows. (1) Problem solving model has better learning achievement than problem posing and direct instruction. Students who were taught by problem posing has better learning achievement than direct instruction, (2) Students who have high learning creativity have the same learning achievement as students who have the medium creativity. Students who have high learning creativity have better learning achievement than students who have low creativity. Students who have medium learning creativity have the same learning achievement as students who have low creativity, (3) Students having high and low creativity that used problem posing, problem solving, and direct instructional model have the same achievement. While students having medium creativity that used problem solving model have better achievement than students that used direct instructional model, but students that used problem posing and problem solving model have the same achievement, and the students that used problem posing and direct instructional model have the same achievement, (4) In each category of learning model, students with high creativity, medium and low have the same learning achievement. Key Words: Problem Posing, Problem Solving, Direct Instruction, Learning Creativity